2020
DOI: 10.1042/bsr20201725
|View full text |Cite
|
Sign up to set email alerts
|

A novel prognostic risk score model based on immune-related genes in patients with stage IV colorectal cancer

Abstract: Purpose: The aims of this study were to explore immune-related genes (IRGs) in stage IV colorectal cancer (CRC) and construct a prognostic risk score model to predict patient overall survival (OS), providing a reference for individualized clinical treatment. Methods: High throughput RNA-sequencing, phenotype, and survival data from patients with stage IV CRC were downloaded from TCGA. Candidate genes were identified by screening for differentially expressed IRGs (DE-IRGs). Univariate Cox regression, LASSO, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In contrast to genetic alterations at DNA level, transcriptional alterations, and expression alterations showed a large variety of observations with little consensus. For example, some studies identified the expression of single markers for prognosis prediction, such as CD133, 27 HSF4, 28 and PLAC1, 29 etc., while other studies identified panels of genes with significant efficacy in prognosis prediction at protein expression levels, mRNA levels or miRNA levels of multiple genes 30–33 . Almost no overlapping of genes was found among the studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to genetic alterations at DNA level, transcriptional alterations, and expression alterations showed a large variety of observations with little consensus. For example, some studies identified the expression of single markers for prognosis prediction, such as CD133, 27 HSF4, 28 and PLAC1, 29 etc., while other studies identified panels of genes with significant efficacy in prognosis prediction at protein expression levels, mRNA levels or miRNA levels of multiple genes 30–33 . Almost no overlapping of genes was found among the studies.…”
Section: Discussionmentioning
confidence: 94%
“…For example, some studies identified the expression of single markers for prognosis prediction, such as CD133, 27 HSF4, 28 and PLAC1, 29 etc., while other studies identified panels of genes with significant efficacy in prognosis prediction at protein expression levels, mRNA levels or miRNA levels of multiple genes. [30][31][32][33] Almost no overlapping of genes was found among the studies. The reason for the huge discrepancies in these studies may involve the large variation of gene transcription and expression profiles across different populations or individuals, the method of tissue sampling, the method for sample treatment and measurement, and the heterogeneity of CRC.…”
Section: The Cancer Tissue Transcriptional Change Was Capable Of Pred...mentioning
confidence: 95%
“…Some advanced cancers have been treated better with immune checkpoint inhibitors (ICIs) [ 40 ]. Boxplots, based on 47 immune checkpoints obtained from the literature [ 41 , 42 ], were used to illustrate the differential expression of immune checkpoints in high-risk and low-risk groups.…”
Section: Methodsmentioning
confidence: 99%
“…The R package “CIBERSORT” was used to estimate the relative proportion of twenty-two types of tumor-infiltrating immune cells (TICs) in each sample ( 28 ). To elucidate the potential role of the constructed gene signature in CC immunotherapy, we inspected the differential expression of 47 immune checkpoint genes between the different NRS-score groups ( 29 ).…”
Section: Methodsmentioning
confidence: 99%